Injil di Tengah Tradisi Santet: Refleksi Misiologis atas Ulangan 18:9-14 dan Budaya Nias Utara - Lumbantoruan, Poda Oky Tober; Mendrofa, Jernita; Telaumbanua, Intan Sari; Illu, Jonidius (Jurnal Teologi Trinity, 2025)
The practice of santet (witchcraft) that still exists within Nias culture reflects a search for spiritual power outside of the living God. In this context, the message of the Gospel faces both a challenge and an opportunity to demonstrate the power of God in Jesus Christ, who brings liberation. This article is a missiological reflection on Deuteronomy 18:9–14, which firmly rejects occult practices, and explores how this passage is relevant in addressing local cultural phenomena such as santet in Nias. Using a theological-contextual approach, this paper analyzes the encounter between the Gospel and local culture, and proposes mission strategies that can reach communities without disregarding their positive cultural values. The proclamation of the Gospel must affirm the authority of God in Jesus Christ, alongside the confidence given to believers through the power of the Holy Spirit to overcome all forces of darkness. At the same time, it must also reveal the love and power of Jesus Christ to heal, restore, and deliver from intimidation. This writing is intended to contribute to the development of mission strategies that are relevant, culturally sensitive, and transformative in communities that continue to wrestle with traditional spiritual powers such as santet.